CAREGIVERS’ EXPERIENCE IN MEETING SELF-CARE NEEDS OF ADOLESCENTS WITH AUTISM SPECTRUM DISORDER: A QUALITATIVE STUDY - Lilis Lestari; Elisabeth Siti Herini; Indria Laksmi Gamayanti (Belitung Nursing Journal, 2017)
Background: Autism spectrum disorder is a complex developmental disorder, which increased rapidly than other developmental disorders in the world. This complex disorder affects a child’s self-autonomy, which has become a challenge for their parents or caregivers. Objective: This study is to explore main caregivers’ experience to meet self-care needs of adolescents with autism spectrum disorder in Pontianak, West Borneo, Indonesia. Methods: This study employed a qualitative design with semi-structured in-depth interviews. Seven main caregivers who are living together and taking care of the adolescents with autism spectrum were selected using a purposive sampling. Triangulation was conducted to ensure the trustworthiness of this study, including interviews, observations of self-care activities, documents such as photos, learning reports, and field notes. Participants’ statements were recorded using a voice recorder, and then transcribed, coded, interpreted, and categorized to form main themes and sub-themes. Results: The study identified three main themes: 1) autonomy in self-care, 2) care effort, 3) feelings, supports, and expectations. These findings emphasize the potentials of the children with autism to be autonomous in their daily self-care. Conclusions: Adolescents with autism spectrum disorder can potentially meet the needs of their daily care independently. This article has been corrected with a separate erratum: https://doi.org/10.33546/bnj.1146